2017
DOI: 10.1536/ihj.16-373
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Ameliorates Arterial Stiffness Assessed by Cardio-Ankle Vascular Index in Patients With Type 2 Diabetes Mellitus

Abstract: SummaryResveratrol has been reported to have potent anti-atherosclerotic effects in animal studies. However, there are few interventional studies in human patients with atherosclerogenic diseases. The cardio-ankle vascular index (CAVI) reflects arterial stiffness and is a clinical surrogate marker of atherosclerosis. The aim of the present study was to investigate the effect of resveratrol on arterial stiffness assessed by CAVI in patients with type 2 diabetes mellitus (T2DM).In this double-blind, randomized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 36 publications
3
66
1
3
Order By: Relevance
“…Several trials have aimed to investigate the antiobesity effects of resveratrol in human. Contrary to our findings, some trials revealed significant effects of resveratrol supplementation on anthropometric measures in patients with T2DM (Imamura et al, 2017;Kumar & Joghee, 2013;Seyyedebrahimi, Khodabandehloo, Esfahani, & Meshkani, 2018). However, one study reached null results (Bo et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Several trials have aimed to investigate the antiobesity effects of resveratrol in human. Contrary to our findings, some trials revealed significant effects of resveratrol supplementation on anthropometric measures in patients with T2DM (Imamura et al, 2017;Kumar & Joghee, 2013;Seyyedebrahimi, Khodabandehloo, Esfahani, & Meshkani, 2018). However, one study reached null results (Bo et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, studies reported that resveratrol contributes to preventing the conversion of LDL-C to oxidized LDL (Liu, Chen, & Li, 2017). However, some human studies failed to show a beneficial effect of resveratrol supplementation (Bashmakov et al, 2014;Imamura et al, 2017). In a study conducted by Crandall et al, no significant change in lipid profile was observed following resveratrol supplementation in older adults (Crandall et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…15) Inducing brown-like adipocyte formation in white adipose tissue (WAT) may be valuable to ameliorate arterial stiffness. 16) Nrg4 was recently identified as a brown-fat-enriched endocrine factor. It could be a key factor for the development of BAT and acquisition of BAT features of WAT depots by promoting the growth of neurites and thus enhancing innervation of the tissues needed to activate the thermogenic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, resveratrol limits the increase in compliance of spontaneously hypertensive rat (SHR) by its inhibitory effect on arterial remodelling and ERK signalling rather than the effect on blood pressure or arterial wall stiffening [82]. In a recent double blind, randomized, placebo-controlled study, resveratrol supplementation has been shown to reduce arterial stiffness (measured by Cardio Ankle Vascular Index) in patients with type 2 diabetes [47].…”
Section: Prevention Of Arterial Stiffeningmentioning
confidence: 99%